O princípio jurídico da coesão dinâmica no Direito Urbanístico brasileiro - Silva, Júlia Maria Plenamente (2016)
The presented thesis is engaged in the principle of dynamic cohesion in Urban Law and order to identify its legal content. The doctrine attributed to the dynamic cohesion nature of autonomous legal principle and content that approaches the system concept itself. Based on the Law General Theory, we start from the analysis of the meaning of the expressions legal principle and legal system. Then move on to the study of the principles of planning and social function of property , we consider fundamental to the identification of Brazilian Urban Law, in order to relate them, especially the principle of planning, to dynamic cohesion. Finally, from the constitutional and infra-constitutional legal norms of urban policy, we will make a proposal of content to be assigned to the principle of dynamic cohesion